Ruby Lu, empress of everything - Look, Lenore; Wilsdorf, Anne (New York : Aladdin Paperbacks, 2007)
After Ruby Lu's deaf cousin, Flying Duck, and her parents come from China to live with her, Ruby finds life challenging as she adjusts to her new family, tries to mend her rocky relationship with her friend Emma, and faces various adventures in summer school.
Book Links (A.L.A.)
Notable/Best Books (A.L.A.)
School Library Journal starred
3.8
K-3.
K-3
Keywords: Chinese Americans -- Fiction; Deaf -- Fiction; Friendship -- Fiction; Immigrants -- Fiction; People with disabilities -- Fiction; Chinese Americans -- Fiction; Deaf -- Fiction; Friendship -- Fiction; Handicapped -- Fiction; Immigrants -- Fiction